Paradigma Keilmuan Dalam Pemikiran Pendidikan Islam Kontemporer Tantangan Dan Prospek - Muhammad AlFarobi; Rahmat Syukur; Latifah Addiba; Dewi Maya Sari (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
The development of creative and dynamic intellectual insights in light and integrated with Islam must be accelerated immediately. The old grudges that continue to be perpetuated and the culture's blind rejection of the West are not wise attitudes. This will only backfire on the intellectual development of Islam. This is where the